Democratic Republic of Sao Tome and Principe : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper focuses on the prospects of growth in Sao Tome and Principe (STP). This case study seeks explanations for STP's relative under-performance and draws lessons for the future. It compares past economic developments in the islands and recommends policies that could most effectively foster future growth in STP. Country-specific characteristics as well as weak institutions contributed to STP's relative underperformance since independence. Initial conditions, particularly regarding human capital and natural resources, contributed to STP's relative underperformance, especially in the first decade after independence. Experience in the four island-states suggests that fiscal discipline, revenue mobilization, and a more active private sector, particularly in the tourism sector, may be key to tap STP's growth potential. Fiscal discipline is needed to contain the fiscal deficit and bring the debt to a sustainable level. Continuing to strengthen public financial management, including implementing multiannual fiscal framework as recommended by the IMF technical assistance, would help.